New communication strategies during COVID-19 in teaching / learning French language - Planelles Iváñez, Montserrat; Sandakova, Elena (The Art of Living, Surviving, Reviving. Studies in Linguistics. The 50th Anniversary of Romance Studies at the University of Łódź, 2022)
The pandemic has brought about a radical change in the educational situation at all levels, to which both teachers and students have had to adapt abruptly. The emotional burden of this situation has been added to all the material and communicative difficulties that have resulted from the states of alarm occurred in all countries worldwide. Thus, the affective factors that are normally involved in the teaching / learning process, which the CEFRL considers under “existential competence”, have been particularly evident in this difficult period in which fear, uncertainty and isolation have been present in all the activities. In this context, the change from face-to-face teaching to blended learning has had a negative influence on the motivation not only of the students but also of the teaching staff. In this article we present the experience in teaching of French as a foreign language of a year in which classroom communication between teacher and student was suddenly and unexpectedly disrupted.*El presente trabajo ha contado con una ayuda del Programa de Redes-I3CE de investigación en docencia universitaria del Instituto de Ciencias de la Educación de la Universidad de Alicante (convocatoria 2020-21). Ref. : 4984.